Fenomena Ekstremisme Di Dunia Pendidikan - Rochim, Ahmad Abdul; Muhammad Wildan; Sembodo Ardi Widodo (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
Extremism is an ideology characterized by excessive fanaticism and rigid views, often manifested through violence against those with differing opinions. In the religious context, extremism arises from a narrow, literal understanding of religious teachings, disregarding their social and historical contexts. The driving factors behind extremism include theological, sociological, and psychological aspects, such as shallow religious understanding, social injustice, and a closed personality. Within educational environments, extremism can spread through indoctrination by certain educators during teaching activities or extracurricular programs. Extremist narratives often exploit the suffering of religious communities and promote violent jihad propaganda. Characteristics of extremists include being closed to other perspectives, harboring negative assumptions, adopting rigid religious practices, and a tendency to label others as infidels. Preventive efforts require the active involvement of the government and educational institutions through regulation, teacher training, and the strengthening of religious moderation values to foster a tolerant and peaceful society